Comparison of Intravitreal Bevacizumab versus Intravitreal Ranibizumab in Treatment Naive Macular Edema Patients (Real World Evidence in Pakistan): http://doi.org/10.36351/pjo.v37i2.1194 - Malik, Hajra Arshad; Sabih, Rayyan; Khan, Hina; Asrar, Aamir; Asif, Muhammad (Pakistan Journal of Ophthalmology, 2021)
Purpose: To compare the short-term efficacy and safety of intraocular Ranibizumab and Bevacizumab in patients with treatment Naïve macular edema. Study Design: Quasi experimental study. Place and Duration of Study: Amanat Eye Hospital, from August 2018 to November 2019. Methods: Patients with macular edema confirmed with optical coherence tomography (OCT) or leakage on fluorescein angiography were included. Patients with NVE, PDR without macular edema and patients who switched to alternative anti-VEGF compounds prior to the completion of three consecutive monthly injections of their respective anti-VEGF or switched to other treatment options were excluded from the study. A thorough clinical examination was conducted including best corrected visual acuity (BCVA, intraocular pressure (IOP), anterior and posterior segment examination and OCT macula. The patients were then allocated to one of the two study arms (either Bevacizumab or Ranibizumab) based on the doctor’s input and patient affordability. All patients underwent three consecutive injections of the selected molecule at one month intervals. BCVA, CRT and macular volume were then recorded 04 weeks after the third injection. Results: A statistically significant mean vision gain was observed from baseline in both groups (p < 0.05). However, the change in BCVA was not significantly different between intravitreal Bevacizumab group and intravitreal Ranibizumab group (p > 0.05). Similarly, although there was improvement in CRT and macular volume in both groups but there was no statistically significant difference between the two. Conclusions: Treatment with intravitreal Bevacizumab and Ranibizumab injections cause statistically similar anatomical and functional results in cases of treatment naïve macular edema. Key Words: Bevacizumab, Ranibizumab, Macular Edema, Diabetic Retinopathy, Macular Degeneration, Retinal Vein Occlusion.